EFEKTIVITAS DAN KEAMANAN TERAPI NATRIUM DIKLOFENAK DAN PIROKSIKAM PADA PASIEN OSTEOARTHRITIS DI PUSKESMAS KOTA SURABAYA: PERBANDINGAN EFEKTIVITAS DAN KEAMANAN NATRIUM DIKLOFENAK DAN PIROKSIKAM PADA PASIEN OSTEOARTHRITIS - Selly Septi Fandinata; Anita Purnamayanti; Primanitha Ria Utami (jurnal ilmiah manuntung sekolah tinggi ilmu kesehatan samarinda, 2020)
Osteoarthritis (OA) is a disorder affecting the diarthrodial joints that support the skeletal system and the axial causing joint symptoms. The effectiveness of NSAID pain therapy in osteoarthritis often results in inadequate response and prolonged use can cause unexpected side effects. The therapy offered is diclofenac sodium and piroxicam. This research used the design of Quasy Experimental Design type Non Equivalent Control Group Design. The research was conducted at Puskesmas Tenggilis Surabaya. The outcomes measured as the intensity of pre and post treatment pain, Drug Side Effects on pre and post-treatment kidney function, and side effects on pre and post-treatment blood pressure. The study sampled 42 patients consisting of 20 patients (piroxicam group) and 22 patients (sodium diclofenac group). There was a significant difference with the intensity of the pain scale in both post groups (p= 0.001). There were no significant differences in average creatinine and BUN in the post treatment of pyroclacycam group and post treatment group sodium diclofenac (p = 0.772) and (p = 0.801). This study shows that the piroxicam group is more effective in reducing the pain scale than sodium diclofenac and both groups have not been shown to be safety in renal function (Creatinine and BUN)